The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings IEEE Thirteenth Annual International Conference on Micro Electro Mechanical Systems (Cat. No.00CH36308)
DOI: 10.1109/memsys.2000.838615
|View full text |Cite
|
Sign up to set email alerts
|

High resolution powder blast micromachining

Abstract: Powder blasting, or Abrasive Jet Machining (AJM), is a technique in which a particle jet is directed towards a target for mechanical material removal. It is a fast, cheap and accurate directional etch technique for brittle materials like glass, silicon and ceramics. By introducing electroplated copper as a new mask material, the feature size of this process was decreased. It was found that blasting with 9 pm particles (compared with 30 pm particles) result in a higher slope of the channel sidewall. The aspect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 11 publications
(4 reference statements)
2
56
0
Order By: Relevance
“…Thus, various non-conventional machining techniques have been applied to the micro-machining of glass; however, the results show the difficulties encountered in the micro-machining of glass. Table 1 shows an overview of available current glass machining techniques and their general capabilities [3]. From Table 1, it can be shown that powder blasting using lithographic masking can be successfully applied to the micro-machining of glass to obtain a small-sized feature with a high aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various non-conventional machining techniques have been applied to the micro-machining of glass; however, the results show the difficulties encountered in the micro-machining of glass. Table 1 shows an overview of available current glass machining techniques and their general capabilities [3]. From Table 1, it can be shown that powder blasting using lithographic masking can be successfully applied to the micro-machining of glass to obtain a small-sized feature with a high aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in Section II we assume a G-MOT type geometry using a 10 mm diameter grating structure and a cavity volume of 15×15×3 mm 3 to avoid light scattering off sidewalls. Around 90% of the beam overlap volume is within 2.5 mm of the grating surface, and so this is a reasonable choice of height and is also feasible to fabricate from silicon using deep reactive ion etching, wet etching, machining, or powder blasting 250 . We have consciously avoided designing the MicroMOT around a single application or manipulation technique, e.g.…”
Section: Prototype Micromotmentioning
confidence: 99%
“…Through-holes are defined using powderblasting [39]- [41]. The Pyrex and silicon wafers are fusion-bonded and annealed at 425 .…”
Section: B Fabricationmentioning
confidence: 99%